The service life increasing of agricultural machinery products by electro-acoustic spraying - Kochetov Andrei; Fisunova Elena; Lavrenova Tatyana; Baryshnikova Olga; Metelkova Nadezhda (E3S Web of Conferences, 2020)
This publication is devoted to the formation of equilibrium conditions in ordered dislocation structures obtained by the influence of highly concentrated electric energy flows and an informal (longitudinaltorsional) ultrasonic field on the conductive substrate material.